Criminal Aspects at the Stages of Registration, Verification and Determination of Political Parties as Candidates for Election Contestants - Riezka Eka Mayasari; La Ode Awal Sakti; Irsan Rahman; Faisal Herisetiawan; Muhamad Aksan Akbar; Yeni Haerani; Basrawi, Basrawi (Dinasti Research, 2024)
This research is motivated by the many forms of criminal acts at each stage of the General Election, one of which can occur at the stages of registration, verification and determination of political parties as potential election participants, as well as different law enforcement mechanisms for election crimes and other criminal acts. It is important to carry out this research with the aim of finding out criminal acts that arise during the stages of registration, verification and determination of political parties as candidate participants in the election and to find out the law enforcement process for criminal acts that occur. The method used in this research is empirical normative which was carried out with literature studies and field studies carried out by the Kolaka Regency Integrated Law Enforcement Center. The results of the research show that the criminal aspects at the stages of Registration, Verification and Determination of Candidates for Election Contestants include criminal acts regulated in the provisions of Article 518 of Law Number 7 of 2017 concerning General Elections (not following up on the findings of Bawaslu, Provincial Bawaslu and/or Regency Bawaslu/ City in carrying out verification of political parties as candidates for Election Contestation), Article 263 of the Criminal Code (Forgery of Documents) and Article 67 of Law Number 27 of 2022 concerning Protection of Personal Data (UU PDP) as well as law enforcement for election crimes is different from criminal acts in general, which using the concept of speedy trial. The things that differentiate include the mechanism for investigation, prosecution and trial which is carried out quickly, can be carried out without the presence of the defendant (in absentia), and legal action can only be taken at the appeal level. In the implementation of handling election crimes at the Kolaka Regency Gakkumdu Center, starting from the Report/Findings Stage, Initial Study, First Discussion, Clarification, Study of suspected violations, Second Discussion, Plenary Meeting, Investigation, Third Discussion, and Prosecution.